1991
DOI: 10.1007/bf01968024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of azithromycin and amoxicillin/clavulanic acid in the treatment of lower respiratory tract infections

Abstract: Forty-eight patients with acute bronchitis and four with pneumonia were randomly assigned to receive five doses (500 mg on day 1, plus 250 mg/day on days 2-5) of azithromycin; 54 patients with acute bronchitis and four with pneumonia were assigned 30 doses (625 mg every eight hours for ten days) of amoxicillin/clavulanic acid (CA). The two regimens were equally effective, with clinical improvement or cure in 92% and 87% of patients respectively, bacteriological cure in 89% and 86%, with 91% and 89% of pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 4 publications
0
14
0
1
Order By: Relevance
“…Amoxicillin/clavulanate has normally been administered as a regimen of 500/125 mg (amoxicillin/clavulanate) every 8 hours for adults. In this regimen, the combination is as effective for treatment of lower respiratory tract infections as other agents such as loracarbef [6,7], cefuroxime [8], and azithromycin [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Amoxicillin/clavulanate has normally been administered as a regimen of 500/125 mg (amoxicillin/clavulanate) every 8 hours for adults. In this regimen, the combination is as effective for treatment of lower respiratory tract infections as other agents such as loracarbef [6,7], cefuroxime [8], and azithromycin [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin has previously been shown to be effective in treating patients with lower respiratory tract infections. Balmes and colleagues observed a favourable clinical response in 44 of 48 (92 %) patients with bacterial cure in 88 % of those who received azithromycin (10). However, the vast majority of patients in that study had acute bronchitis rather than pneumonia.…”
Section: Gens (Haemophilus Influenzae Moraxella (Branhamella) Catarrmentioning
confidence: 94%
“…In addition, in animal models of infection, azithromycin has been shown to be effective against the respiratory pathogens, Haemophihts influenzae, Streptococcus pneumoniae and Legionella pneumophila (8,9). A recent study demonstrated that azithromycin was comparable to anaoxicillin/clavulanic acid in a multicentre trial in 110 patients with bronchitis or pneumonia caused by Haemophilus influenzae, Haemophilus parainfluenzae, Streptococcus pneumoniae and Staphylococcus aureus (10). Clinical cure occurred in 36 of 48 patients (75 %) on azithromycin and clinical improvement in 8 of 48 (17 %).…”
mentioning
confidence: 96%
“…The clinical and bacteriological results of selected trials are summarized in Table 4 [140][141][142][143][144][145][146][147][148][149][150]. Overall, clinical success rates ranging from 81-100 and 86-97% were observed with azithromycin and clarithromycin, respectively; bacteriological success ranged from 80-94 and 89-95% respectively.…”
Section: Advantagesmentioning
confidence: 99%